Znanost in ideologija - Ličer, Matjaž (Primerjalna književnost, 2012)
Today we are witnessing a quite common Manichean break-up of science on natural sciences and the humanities. Natural sciences play the role of useful,clinically clean, objective and exact activity, while humanism is reduced to a useless conglomerate of subjective, ideologically motivated constructs. Following Althusser, I aim to show that this delineation is false - not because humanism is not entangled with ideologies, but because the same holds for science: scientists are as scientists not immune to their personal beliefs and worldviews that can always be reduced to very concrete positions within philosophy (say, Spinozism in Einstein's case, rationalism in Gödel's, or materialism in Heisenberg's). I claim that the break-up of science leads toan illegitimate naturalisation of society that serves as the framework of the neoliberal worldview within science and other fields.
Keywords: materialistična filozofija; naravoslovne znanosti; humanistika; ideologija; neoliberalizem